Let's look at leeks! Picture books increase toddlers' willingness to look at, taste and consume unfamiliar vegetables - Heath, Philippa; Houston-Price, Carmel; Kennedy, Orla (Frontiers in Psychology, 2014)
Repeatedly looking at picture books about fruits and vegetables with parents enhances young children's visual preferences toward the foods in the book (Houston-Price et al., 2009a) and influences their willingness to taste these foods (Houston-Price et al., 2009b). This article explores whether the effects of picture book exposure are affected by infants' initial familiarity with and liking for the foods presented. In two experiments parents of 19- to 26-month-old toddlers were asked to read a picture book about a liked, disliked or unfamiliar fruit or vegetable with their child every day for 2 weeks. The impact of the intervention on both infants' visual preferences and their eating behavior was determined by the initial status of the target food, with the strongest effects for foods that were initially unfamiliar. Most strikingly, toddlers consumed more of the unfamiliar vegetable they had seen in their picture book than of a matched control vegetable. Results confirm the potential for picture books to play a positive role in encouraging healthy eating in young children.